PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA NON FISIK DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN SALES PT NASMOCO SLAMET RIYADI SURAKARTA - Darmawan, Dicky; Lamidi, Lamidi (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The purpose of this study was to analyze the effect of leadership style, non-physical work environment and work discipline on the performance of sales employees. This type of research is census research on Sales division employees at PT Nasmoco Slamet Riyadi Surakarta. The study population amounted to 34 people and all were used as samples with population research techniques. Data collection techniques using questionnaires and literature studies. Data analysis techniques using multiple linear regression methods, t test, F test and coefficient of determination. The results showed that leadership style has a significant effect on the performance of employees of PT Nasmoco Slamet Riyadi in Surakarta. Non-physical work environment has a significant effect on the performance of employees of PT Nasmoco Slamet Riyadi in Surakarta. Work discipline has a significant effect on the performance of employees of PT Nasmoco Slamet Riyadi in Surakarta. The results of the coefficient of determination obtained adjusted R square value of 0.847, this means that the influence of leadership style variables, non-physical work environment and work discipline on the performance of sales employees is 84.7% while 15.3% is influenced by other variables outside the research model, such as salary, job satisfaction and work motivation.